School-aged children's movement behaviours and subjective health complaints in Japan: a cross-sectional study during COVID-19 pandemic-related school closures and after school reopenings - Akane Kasai; Akiko Shikano; Ryo Tanaka; Mari Yoshinaga; Shingo Noi (BMC, 2024)
Abstract Background Social restrictions associated with the COVID-19 pandemic have altered children's movement behaviours and impacted their mental health. However, the influence of social restrictions on subjective health complaints remains inadequately understood. This study compared adherence to 24-hour movement behaviour guidelines and the prevalence of subjective health complaints during school closure and one year after reopening. We also examined how combinations of adherence to movement behaviour recommendations relate to subjective health complaints. Methods A repeated cross-sectional survey was conducted at two points. The first survey in May 2020 included 1535 (766 boys and 769 girls) participants during school closures, while the second survey from May to July 2021 involved 1125 (583 boys and 542 girls) participants one year after school reopening. The questionnaire covered socio-demographics, physical activity, screen time, sleep, and subjective health complaints. Differences between periods were analysed using chi-square tests. Logistic regression models assessed the association between adherence to guidelines and subjective health complaints. Results During school closure, children were more likely to meet 'only sleep' recommendations and have irritability and lethargy symptoms. Irrespective of sex, those adhering to two or all three recommendations (excluding physical activity and screen time) had a lower risk of symptoms related to physical and mental pain, fatigue, irritability, and lethargy as compared to those who met none of the recommendations. Conclusions Children should meet at least one physical activity or screen time recommendation in addition to sleep recommendations for subjective health. Strategies considering the priority of each movement behaviour are crucial, even during abnormal situations, such as pandemic-related social restrictions. This study offers insightful findings concerning children's mental health issues during unprecedented and massive disasters or crises.